Entre o antigo e o novo: a narrativa dos mototaxistas e o uso de aplicativos de transporte em Juazeiro do Norte, Ceará - Benjamim, Rafaela Pereira (2024)
Over the last few years, mainly in cities in the interior of the state of Ceará, given the absence of urban mobility policies, a series of passenger transport alternatives have been created, many of them without any regulation or monitoring by official bodies. In this work we will study the change in the activity of self-employed motorcycle taxi drivers to the activity linked to transport app platforms, highlighting the workers' perception of this transformation. The research problem is related to changes in the labor dynamics of these workers in the city of Juazeiro do Norte -CE. Some categories/concepts will be necessary to carry out this analysis. Topics such as: platformization of work, neoliberalism, deskilling of labor, informality, precariousness and data about the city where the research will be based are covered. In view of this, the present research has the general objective: Analyze the understanding of workers who work in the transport activity with a focus on the transition from motorcycle taxi driver to app workers in the city of Juazeiro do Norte- CE. With specific objectives: Analyze how the activity of motorcycle taxi drivers was configured in the city of Juazeiro do Norte, before the arrival of the applications; Identify the main aspects that led to the change in activity from motorcycle taxi drivers to app-based workers and, finally, highlight the current app-based working conditions in the perception of these workers. The analysis proposal is qualitative in nature and, for this purpose, Bardin's content analysis will be used. The interviews were carried out between April and May 2024. As a result, the perceptions of transport workers are highlighted in relation to the difficulties and impacts encountered in the daily activity they perform based on the changes made in the work organizational process.